Controlled Protective Layer Based on Biphenyl Derivatives for Li-S Battery. Issue 8 (8th May 2019) - Vinci, Valentin; Alloin, Fannie; Guindet, Jacques; Leprêtre, Jean-Claude
Abstract : The current development of Li-S batteries is still hindered by some challenging issues, such as poor cyclability and low coulombic efficiency partially related to the unavailing passivation of metallic lithium electrode. This paper deals with the use of the biphenyl chemistry for forming an in situ protective layer at the lithium interface. We have put in evidence that the use of the poly(4-vinyl biphenyl) permits to form a protective layer which improves notably the cyclability and the coulombic efficiency of the Li-S system.